A história da alimentação como ferramenta de ensino de história - Oliveira, Adriana Sassi de (2018)
The present study proposes the development of possibilities for teaching through the History of Food as a proposal of historical learning. Such theme was chosen for its relevance as well as its potential to contribute to students' understanding of History as a school subject, since food is an intrinsic element of humanity history, thus being a guiding thread capable of provoking inquiries, identifying relations between the past and the present, arousing interest, understanding and reflection, enhancing an intersection between historical, social and cultural elements. For the accomplishment of this study, several theoretical references were used, allowing a greater theoretical investigation regarding this approach. The application and investigation were conducted in two public schools, comprising an Elementary as well as a High School, both located in Santa Maria, in the state of Rio Grande do Sul, Brazil. One of the goals was to verify how the same teaching proposal and the same programmatic content: "The Medieval World", could be understood and perceived in these two different levels of education. Multiple sources and resources were used in order to favor an innovative practice, arousing students’ interest in History, making it enjoyable and meaningful. For the accomplishment of this work, several instruments have been used to promote an interaction between students and the historical content. Firstly, an exposition of the medieval context investigated was proposed, using various iconographic materials to promote debates in class. Afterwards, data collection was carried out among students and their families, who answered questions related to eating habits and customs for comparison purposes, in order to perceive the relations of similarities and differences between the generations examined, with the final aim of relating them to the medieval context. To demonstrate this perception, students prepared a Medieval Table, exposing foods which are still present nowadays. The conclusion of this study was conducted through a Class Memory, in which students recorded their understandings acquired through the approaches proposed for historical learning. The results obtained confirmed that all the objectives initially indicated in the present work have been achieved. It is possible to conclude that the present proposal of historical learning, valuing local memory and experiences, besides facilitating comparisons with the past, was able to successfully approximate students’ reality to History, making historical teaching and knowledge constructive and interesting.